Series of 7 pictures. Stalls of the East London Federation of the Suffragetes in Roman Road with the announcement of the procession and meeting in Canning Town on July twelfth
Series of 7 pictures. Stalls of the East London Federation of the Suffragetes in Roman Road with the announcement of the procession and meeting in Canning Town on July twelfth.